UiO-66 Selective Enrichment Integrated with Thermal Desorption GC-MS for Detection of Benzene Homologues in Ambient Air - Xing-Tao Lin; Ge Sun; Jing-Qiang Zhao; Ling-Li Tang; Sheng-Hua Li; Ya-Bo Xie (Journal of Analytical Methods in Chemistry)
In this study, UiO-66 was selected as sorbent media packed in the tube to selectively enrich trace levels of benzene homologues such as benzene, toluene, and xylene (BTX) in ambient air prior to thermal desorption (TD)-GC-MS determination. A series of experiments were conducted to obtain the optimal TD conditions. The results indicated that the optimal TD parameters were as follows: desorption temperature of 180°C, desorption flow rate of 50 mL min−1, and desorption time of 30 min. Furthermore, the method based on UiO-66 enrichment integrated with TD-GC-MS for trace levels of BTX was successfully developed. It exhibited a good linearity (R2 > 0.99) in the range of 50–1000 ng, except for p, m-xylene in the range of 100–2000 ng, and achieved the recovery of 69.4–101.3%, and the relative standard deviation of 3.8–6.4%. The detection limits of BTX were 1.6–4.0 ng; according to 10 L of sampling volume, the method detection limits would be in the range of 0.16–0.40 µg m−3. Additionally, the method was successfully applied to determine BTX in indoor air and showed good selectivity and sensitivity. In summary, the findings in this work revealed that UiO-66 was an attractive adsorbent for selective enrichment trace levels of BTX compounds in ambient air, which was favorable for the subsequent detection by TD-GC-MS.